A Cole Porter Companion - Weiss, Susan Forscher; Shaftel, Matthew R.; Randel, Don Michael (Book collections on Project MUSE., 2016)
Balancing sophisticated melodies and irresistible rhythms with lyrics by turns cynical and passionate, Cole Porter sent American song soaring. Timeless works like 'I Get a Kick Out of You' and 'At Long Last Love' made him an essential figure in the soundtrack of a century and earned him adoration from generations of music lovers. This work offers essays on little-known aspects of the master tunesmith's life and art.